Penerapan Teaching Practic Seni Rupa pada Anak Usia Dini - Octavia, Fadilla Mizratul; Balqis, Aisyah Shinta; Lestari, Juli; Seisky, Seisky; Fauza, Hilyatul; Khaira, Ummi; Deswita, Miranda; Dewi, Ayu Citra (Journal Education And Islamic Studies, 2024)
This study aims to identify the role of art in early childhood learning, evaluate the effectiveness of the learning approach through play with art with the research theme "Implementation of Teaching Practice of Fine Arts in Early Childhood". This article investigates the impact of art integration in learning on the development of early childhood. The research method used is qualitative using the theory of PTK in the classroom, which focuses on art as a learning tool for early childhood in the context of learning through play. Experiments were conducted with various art media, namely: finger painting, inner and outer smearing, batik using tissue, Cotton bud, painting using cotton bud, gradation, drawing with crayons. Data were analyzed using Quasi-experimental experiments to identify the main themes related to the role of art in learning and learning through play. In the implementation of the study, it was found that the role of art in learning and the effectiveness of the learning approach through play had a significant positive impact on the development of fine motor skills, creativity, and emotional and psychological responses of children. Furthermore, the results of this study emphasize the importance of art integration in preschool education to enrich the learning experience of early childhood and support the overall growth of children.